Effects of the 5-m shuttle run test on markers of muscle damage, inflammation, and fatigue in healthy male athletes - Boukhris, Omar; Trabelsi, Khaled; Abdessalem, Raouf; Hsouna, Hsen; Ammar, Achraf; Glenn, Jordan M.; Bott, Nick; Irandoust, Khadijah; Taheri, Morteza; Turki, Mouna; Ayadi, Fatma; Bragazzi, Nicola L.; et al. (International journal of environmental research and public health, 2020)
Physical exercise is often associated with increases in muscle damage markers and inflammation. However, biomarkers of muscle damage and inflammation responses to the 5-m shuttle run test (5mSRT) have not yet been evaluated. The aim of the present study was to investigate effects of the 5mSRT on muscle damage markers, inflammation, and perception of fatigue and recovery in healthy male athletes. Fifteen male amateur team sports players (age: 20 ± 3 yrs, height: 173 ± 7 cm, body-mass: 67 ± 7 kg) participated in this study. Blood biomarkers were collected at rest, 5 min after, and 72 h after the 5mSRT to measure muscle damage (i.e., creatinine kinase (CK), lactate dehydrogenase (LDH), aspartate aminotransferase (ASAT), and alanine aminotransferase (ALAT)) and inflammation (i.e., C-reactive protein (CRP)). Best distance (BD), total distance (TD), fatigue index (FI), and percentage decrement (PD) during the 5mSRT were assessed. Perceived recovery (PRS) and delayed onset muscle soreness (DOMS) were recorded before, 5 min after, and 72 h after the 5mSRT; perceived exertion (RPE) was recorded before, during, and 72 h after the 5mSRT. Muscle damage biomarkers post 5mSRT showed a significant increase compared to pre 5mSRT (p < 0.001) levels ((i.e., CK (190.6 ± 109.1 IU/L vs. 234.6 ± 113.7 IU/L), LDH (163.6 ± 35.1 IU/L vs. 209.9 ± 50.8 IU/L), ASAT (18.0 ± 4.4 IU/L vs. 21.7 ± 6.2 IU/L), and ALAT (10.2 ± 3.4 IU/L vs. 12.7 ± 3.8 IU/L)) and 72 h post 5mSRT (p < 0.001) levels ((CK (125.3 ± 80.5 IU/L vs. 234.6 ± 113.7 IU/L), LDH (143.9 ± 36.6 IU/L vs. 209.9 ± 50.8 IU/L), ASAT (15.0 ± 4.7 IU/L vs. 21.7 ± 6.2 IU/L), and ALAT (8.6 ± 2.4 IU/L vs. 12.7 ± 3.8 IU/L)). CRP was also significantly higher post 5mSRT compared to pre 5mSRT (2.1 ± 2.5 mg/L vs. 2.8 ± 3.3 mg/L, p < 0.001) and 72 h post 5mSRT (1.4 ± 2.3 mg/L vs. 2.8 ± 3.3 mg/L, p < 0.001). Significant correlations were reported between (i) physical performance parameters (i.e., PD, FI, TD, and BD), and (ii) markers of muscle damage (i.e., CK, LDH, ASAT, and ALAT) and inflammation (i.e., CRP). Similarly, DOMS and RPE scores were significantly higher post 5mSRT compared to pre 5mSRT (2.4 ± 1.0UA vs. 6.7 ± 1.1UA and 2.1 ± 0.6 UA vs. 8.1 ± 0.6 UA, respectively p < 0.001) and 72 h post 5mSRT (1.9 ± 0.7 UA vs. 6.7 ± 1.1 UA and 1.5 ± 0.6 UA vs. 8.1 ± 0.6 UA, respectively p < 0.001). PRS scores were significantly lower post 5mSRT as compared to pre 5mSRT (6 ± 1 UA vs. 3 ± 1 UA, p < 0.001) and 72 h post 5mSRT (7 ± 1 UA vs. 3 ± 1 UA, p < 0.001). Significant correlations existed between (i) performance parameters (PD, FI, TD, and BD) and (ii) RPE, PRS, and DOMS. The 5mSRT increased biomarkers of muscle damage and inflammation, as well as the DOMS and RPE and reduced the PRS. Seventy-two hours was sufficient for fatigue recovery induced by the 5mSRT. PD is better than FI for the calculation of performance decrements during the 5mSRT to represent fatigue.
Gesehen am 07.09.2020